2022
DOI: 10.3389/fsurg.2022.1016278
|View full text |Cite
|
Sign up to set email alerts
|

Combining portable coagulometers with the Internet: A new model of warfarin anticoagulation in patients following mechanical heart valve replacement

Abstract: Heart valve replacement, as a safe and effective treatment for severe valvular heart disease, can significantly improve hemodynamics in patients. However, such patients then require lifelong anticoagulant therapy. Warfarin, a cheap and highly effective vitamin K antagonist, remains the major anticoagulant recommended for lifelong use following mechanical heart valve replacement. However, the effect of warfarin anticoagulant therapy is complicated by physiological differences among patients and non-compliance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Currently, researchers have shown interest in developing anticoagulant health management models using the internet and smart devices with a focus on self-management. Huang et al ( 14 ) proposed an anticoagulant management model with a portable coagulator and online medical communication, allowing patients to monitor the international normalized ratio at home and enabling online consultations. Zhu et al ( 44 ) suggested the development of a warfarin anticoagulation follow-up system after valve replacement surgery and compared the internet-based warfarin anticoagulation management model with the traditional warfarin management model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, researchers have shown interest in developing anticoagulant health management models using the internet and smart devices with a focus on self-management. Huang et al ( 14 ) proposed an anticoagulant management model with a portable coagulator and online medical communication, allowing patients to monitor the international normalized ratio at home and enabling online consultations. Zhu et al ( 44 ) suggested the development of a warfarin anticoagulation follow-up system after valve replacement surgery and compared the internet-based warfarin anticoagulation management model with the traditional warfarin management model.…”
Section: Discussionmentioning
confidence: 99%
“…The management of patients undergoing valve replacement includes hospital-based and self-management approaches, which aim to achieve optimal long-term outcomes through periodic monitoring and timely intervention ( 13 ). Various intelligent rehabilitation health management strategies, such as wearable monitoring devices, self-management applications, and Internet Plus, have emerged in recent years in medical care ( 14 16 ). Thus, gaining insight into the trends and identifying future opportunities in managing patients undergoing valve replacement may promote mobile intelligent health management, provide an integrated and innovative service mode, and achieve optimal health management.…”
Section: Introductionmentioning
confidence: 99%